(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2026)
The research aimed to evaluate the elasticity of agricultural inputs in citrus production in the Lattakia region for the year 2024, with the aim of improving resource utilization efficiency and enhancing economic returns. The research used descriptive analytical and quantitative approaches, using Cobb-Douglas function estimation and data from a random sample of 159 farmers. The results showed that the total production costs of one dunum amounted to approximately 48,002 thousand Syrian pounds, with variable costs accounting for 58%. Fixed costs constituted 42% of the total. The elasticity coefficients indicated that irrigation water and manual labor had the highest positive impact on yield increases, while organic fertilizers had a moderate impact. The marginal economic efficiency of mineral fertilizers and pesticides was low, reflecting the potential for improving the allocation of these resources. The overall economic efficiency reached 1.07, and the economic profitability reached 6.46%, demonstrating the ability of farmers to achieve profitable returns despite high costs. The study recommended the need to rationalize the use of inputs through laboratory soil analysis, develop irrigation methods, and improve transportation and marketing management.